1995 IEEE 45th Vehicular Technology Conference. Countdown to the Wireless Twenty-First Century
DOI: 10.1109/vetec.1995.504962
|View full text |Cite
|
Sign up to set email alerts
|

Voice quality of interconnected North-American cellular, European cellular, and public switched telephone networks

Abstract: The non-linear nature of low-rate parametric speech coding has rendered questionable analytical methods for estimating the end-to-end voice quality of interconnected telecommunications networks. Instead, quantification of transmission performance appears to require direct subjective evaluation of the pertinent conditions of interest. At the same time, the rapid growth of cellular communications has highlighted the need to characterize the quality of switched networks when cellular terminals are attached at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Calls will thus be established over multi-link circuits employing different types of speech The characteristics of interconnected voice links were recently a subject of investigation [59,60,61] resulting in considerable attention been given to the interconnection characteristics of new voice coding technology. These concerns have, of course been heightened by the wider mix of voice coding technology arising from a proliferation of proprietary, regional, and international standards; by the increasing wireless network access, promising to reach 50% by the end of the century; by the increasing use of wireless local loops in developing countries as a means to accelerate network deployment; and by the accelerating telecommunications network deregulation and privatization resulting in a larger number of network links with disparate technologies being encountered in end-to-end connections.…”
Section: Concatenated Speech Codingmentioning
confidence: 99%
See 1 more Smart Citation
“…Calls will thus be established over multi-link circuits employing different types of speech The characteristics of interconnected voice links were recently a subject of investigation [59,60,61] resulting in considerable attention been given to the interconnection characteristics of new voice coding technology. These concerns have, of course been heightened by the wider mix of voice coding technology arising from a proliferation of proprietary, regional, and international standards; by the increasing wireless network access, promising to reach 50% by the end of the century; by the increasing use of wireless local loops in developing countries as a means to accelerate network deployment; and by the accelerating telecommunications network deregulation and privatization resulting in a larger number of network links with disparate technologies being encountered in end-to-end connections.…”
Section: Concatenated Speech Codingmentioning
confidence: 99%
“…DCME equipments have been slowly migrating to the use of 16 kbps LD-CELP which is shown in configuration B. Configuration C is the case of a call from North American cellular user to a European cellular user. The results of subjective tests [61] using such interconnection indicated that voice quality in the link of Configuration C was degraded by more than 1.0 of a MOS compared to the MOS of weakest portion of the link, namely 13 kbps RPE-LTP. Since the results shown were obtained with an accuracy of 0.1 of an MOS at a 95% level of confidence, and since an MOS drop of more than 0.3 is typically associated with a "new class" of service quality, it can be seen that the impact of PSTN interconnections is to produce an end-to-end connection whose quality differs markedly from that where no such interconnections exist.…”
Section: Concatenated Speech Codingmentioning
confidence: 99%